Population differentiation between Australian and Chinese Helicoverpa armigera occurs in distinct blocks on the Z-chromosome. Issue 6 (5th February 2018) - Song, S.V.; Anderson, C.; Good, R.T.; Leslie, S.; Wu, Y.; Oakeshott, J.G.; Robin, C.
Abstract: Over the last 40 years, many types of population genetic markers have been used to assess the population structure of the pest moth species Helicoverpa armigera . While this species is highly vagile, there is evidence of inter-continental population structure. Here, we examine Z-chromosome molecular markers within and between Chinese and Australian populations. Using 1352 polymorphic sites from 40 Z-linked loci, we compared two Chinese populations of moths separated by 700 km and found virtually no population structure ( n = 41 and n = 54, with <1% of variation discriminating between populations). The levels of nucleotide diversity within these populations were consistent with previous estimates from introns in Z-linked genes of Australian samples (π = 0.028 vs. 0.03). Furthermore, all loci surveyed in these Chinese populations showed a skew toward rare variants, with ten loci having a significant Tajima's D statistic, suggesting that this species could have undergone a population expansion. Eight of the 40 loci had been examined in a previous study of Australian moths, of which six revealed very little inter-continental population structure. However, the two markers associated with the Cyp303a1 locus that has previously been proposed to be a target of a selective sweep, exhibited allele structuring between countries. Using a separate dataset of 19 Australian and four Chinese moths, we scanned the molecular variation distributed across the entire Z-chromosome and found distinct blocks of differentiation that include the region containing Cyp303a1 . We recommend some of these loci join those associated with insecticide resistance to form a set of genes best suited to analyzing population structure in this global pest.